Levels of apolipoprotein A-II in cerebrospinal fluid in patients with neuroborreliosis are associated with lipophagocytosis - Táborský, L; Adam, P; Sobek, O; Dostál, M; Dvoráková, J; Dubská, L (Folia microbiologica, 2003)
Levels of most of the examined proteins in cerebrospinal fluid (CSF) of 107 patients with neuroborreliosis were associated with cytological findings, the status of hematoencephalic barrier as evaluated by Qalb (cerebrospinal fluid to serum quotient) and the intrathecal synthesis of immunoglobulins. Cytological findings consisted of normal cytology, or both oligocytosis and pleocytosis of monocytes or lymphocytes. The lipophagic elements were present in 20% of samples. Concentrations of apolipoproteins A-I and A-II in the CSF were correlated with the concentration of albumin without regard to the CSF cytology. The levels of apolipoprotein B were increased only in samples with lymphocytic pleocytosis and Qalb > 7.4. The presence of lipophages in the CSF was significantly associated with the CSF concentration of apolipoprotein A-II.
Keywords: dospělí; ženské pohlaví; mladiství; Lyme Neuroborreliosis; lidé; Female; imunoglobulin G; imunoglobulin M; lymfocyty; Aged, 80 and over; senioři; Phagocytosis; Aged; Child; lidé středního věku; senioři nad 80 let; apolipoprotein A-I; Humans; apolipoprotein A-II; imunoglobulin A; fagocytóza; mužské pohlaví; Adult; Apolipoprotein A-II; Immunoglobulin G; Male; lymská neuroborelióza; Monocytes; Adolescent; monocyty; Middle Aged; Apolipoprotein A-I; dítě; Immunoglobulin A; Lymphocytes; Immunoglobulin M